2004
DOI: 10.1055/s-2004-815863
|View full text |Cite
|
Sign up to set email alerts
|

Handlebar Hernia in Children: Two Cases and Review of the Literature

Abstract: Localised traumatic abdominal hernias are rare. Most such hernias are due to the direct impact of the handlebars of a bicycle or motorcycle, with 20 cases reported to date in the English language literature, 12 in children. We report two new cases of handlebar hernia, in children aged 6 and 10 years. In both cases, physical examination revealed an area of contusion and bruising in the lower abdomen. However, the muscle defect was detected during the first examination in only one of the patients, and not until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The spectrum of injuries we encountered (Table 1) is comparable to other studies in pediatric patients where parenchymatous organ lesions were found in up to 30 %, intestinal perforations in up to 10 % [13,14], and traumatic abdominal wall hernia in up to 20 % [15] and are also described in adults [16]. Traumatic thoracic wall hernias are very rare [17,18].…”
Section: Discussionsupporting
confidence: 85%
“…The spectrum of injuries we encountered (Table 1) is comparable to other studies in pediatric patients where parenchymatous organ lesions were found in up to 30 %, intestinal perforations in up to 10 % [13,14], and traumatic abdominal wall hernia in up to 20 % [15] and are also described in adults [16]. Traumatic thoracic wall hernias are very rare [17,18].…”
Section: Discussionsupporting
confidence: 85%
“…Computed tomography and US were useful for detecting the disruption of the abdominal wall musculature or the prolapsed intestine. [1][2][3][4][5][6][7][8][9][10][11] In our patient, no prolapsed bowel was found, but a disruption of the abdominal wall musculature was clearly seen on the CT scan. If the disruption of abdominal wall muscles is unclear, local dilated intestinal loops might indicate intestinal obstruction or herniation into the abdominal wall.…”
Section: Case Reportmentioning
confidence: 55%
“…The handlebar hernia of our patient resolved within 3 weeks with an abdominal bandage; however, because a case of delayed appearance of TAWH was reported, careful follow-up is important. 6,13,14 In conclusion, the possibility of handlebar hernia should always be considered in children who have suffered abdominal trauma in a bicycle accident.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations